Effects of electrohydroimpulse discharges on the crushing of the natural mineral quartz - Bulkairova, G.A.; Stoev, M.; Khassenov, A.K.; Karabekova, D.Zh.; Nurgaliyeva, Zh.G.; Kipshakov, M.S. (Eurasian Physical Technical Journal, 2019)
Electro-hydro-impulse (high-current discharge in water) also belongs to the technologies using strong impulse currents. With a powerful pulsed electric discharge between the electrodes placed in the liquid, an electro-hydraulic effect occurs. To study the influence of electro-hydro-pulse shock waves were designed and assembled the experimental setup. The dependences of the degree of grinding of natural mineral quartz on the electro-technical parameters of the discharges are given. The optimal conditions for the most intensive grinding of natural mineral quartz using electro-hydro-pulse treatment are determined. © 2019 E.A.Buketov Karaganda State University Publish House. All rights reserved.
Keywords: Degree of grinding; Electro-hydraulic effect; Natural mineral quartz; Underwater electric discharge